2020
DOI: 10.3390/mi11020163
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Recessed Gate AlGaN/GaN MIS-HEMTs with Double AlGaN Barrier Designs toward an Enhancement-Mode Characteristic

Abstract: In this work, recessed gate AlGaN/GaN metal-insulator-semiconductor high-electron-mobility transistors (MIS-HEMTs) with double AlGaN barrier designs are fabricated and investigated. Two different recessed depths are designed, leading to a 5 nm and a 3 nm remaining bottom AlGaN barrier under the gate region, and two different Al% (15% and 20%) in the bottom AlGaN barriers are designed. First of all, a double hump trans-conductance (gm)–gate voltage (VG) characteristic is observed in a recessed gate AlGaN/GaN MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…But HEMT and MOSHEMT based devices suffer from high contact and high on-resistance due to metallic ohmic contacts and significant source/drain distance. However, the modified gate structure reduces the gate resistance while maintaining the modified gate length and reduced the gate capacitance [13][14][15][16][17]. Generally, AlGaN/GaN HEMTs are normally-on devices and operates in depletion mode.…”
Section: Introductionmentioning
confidence: 99%
“…But HEMT and MOSHEMT based devices suffer from high contact and high on-resistance due to metallic ohmic contacts and significant source/drain distance. However, the modified gate structure reduces the gate resistance while maintaining the modified gate length and reduced the gate capacitance [13][14][15][16][17]. Generally, AlGaN/GaN HEMTs are normally-on devices and operates in depletion mode.…”
Section: Introductionmentioning
confidence: 99%
“…GaN-based high electron mobility transistors (HEMTs) are good candidates for high frequency and high efficiency power switching applications owing to their attractive superiorities of high breakdown electric field and high saturation electron velocity [ 1 ]. Normally-off property is strongly required for GaN devices used in the power electronics systems.…”
Section: Introductionmentioning
confidence: 99%
“…It was already demonstrated that the combination of these two approaches ('gate recess' and 'gate oxide') leads to a further device performance improvement [6,[48][49][50][51][52][53][54][55]. Furthermore, extensive studies have been performed on the influence of material growth, layer design and processing technology on device performance, however little attention was paid to the effects of the amorphous dielectric AlN layer in gate recessed MISHFET AlGaN/GaN structures on strain as well as on the electrical characteristics.…”
Section: Introductionmentioning
confidence: 99%